Robust attitude tracking control of spacecraft under control input magnitude and rate saturations. (25th March 2015) - Zou, An‐Min; Kumar, Krishna Dev; de Ruiter, Anton H. J.
Summary: This paper investigates the problem of attitude tracking control of spacecraft subject to control input magnitude and rate saturations. The smooth hyperbolic tangent function is used to model the magnitude and rate saturations. As the system is non‐affine in the control input, an augmented plant is presented to facilitate the development of the control law. The backstepping technique, robust control and adaptive control approaches are applied to design the control law. The stability of the closed‐loop system is guaranteed by the Lyapunov method. Numerical simulations are presented to demonstrate the performance of the proposed controller. Copyright © 2015 John Wiley & Sons, Ltd.